Nitrogen-doped Ni2P/Ni12P5/Ni3S2 three-phase heterostructure arrays with ultrahigh areal capacitance for high-performance asymmetric supercapacitor. (10th October 2021) - Qin, Yaohua; Lyu, Yizhi; Chen, Mingyue; Lu, Yu; Qi, Pengcheng; Wu, Hao; Sheng, Zhuwei; Gan, Xueling; Chen, Zhigang; Tang, Yiwen
Abstract: Transition metal phosphides and sulfides are considered to be promising electrode materials for supercapacitors due to their excellent electrochemical properties, and the construction of heterostructures is proved to be an effective strategy to improve the electrochemical performances of materials. Herein, curved and rough flake-like nitrogen-doped Ni2 P/Ni12 P5 /Ni3 S2 heterostructure arrays on Ni foam are prepared successfully through gas-phase phosphorization, sulfurization and nitrogen doping simultaneously using Ni(OH)2 nanosheets as precursors under low temperature. The fabricated electrode exhibits an ultrahigh areal capacitance of 19.57 F cm −2 at current density of 2 mA cm −2, and high-rate capabilities, showing excellent capacitance performance. The supercapacitor assembled with nitrogen-doped Ni2 P/Ni12 P5 /Ni3 S2 as a positive electrode can achieve a maximum areal capacitance of 2.77 F cm −2 with a maximum energy density of 0.984 mWh cm −2 . Besides, the supercapacitor has a capacitance retention rate of 110% after 5000 cycles at a large current density of 100 mA cm −2, showing excellent cycling stability. This work demonstrates a rational design and tuned fabrication of composites of transition metal phosphides/sulfides for stable and high-rate energy storage.